Exercise, orthoses and splinting for treating Achilles tendinopathy - Wilson, Fiona (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effects (benefits and harms) of exercise, orthoses and splinting for treating Achilles tendinopathy. We will compare each of the three intervention categories (exercise, orthoses, splinting) with no intervention, a placebo intervention or advice to rest; and with each other. We will also compare different types, applications and modes of delivery of interventions within the three intervention categories.